Defending Democracy Through Democracy Defenders Accelerator Bootcamp in Estonia - Al-Fatih, Sholahuddin; Hirmo, Meelika (Universitas Muhammadiyah Malang, 2024)
Democracy is becoming mainstream in modern countries. Even though many people choose it, implementing democracy does not always run smoothly. Some countries show inappropriate democratic practices. Through this international community service, the service tries to share stories with the world about the practice of democracy in Indonesia, especially for the younger generation. This community service agenda will occur in Estonia from March 27 to April 5, 2023. The service method is a mixed model, with socialization sessions, discussions, and class material. It is hoped that the results of this service will provide benefits to democracy activists throughout the world. Maintaining democracy requires methods and strategies, such as strengthening godship values ​​in legal products, both at the central and regional levels, accommodating developing values ​​and culture in society as living law, and protecting oneself from values ​​not by the identity of the nation and state. Abstrak Membela Demokrasi Melalui Pelatihan Akselerator Pembela Demokrasi di Estonia Demokrasi menjadi arus utama bagi negara-negara modern. Meskipun banyak dipilih, implementasi demokrasi tidak selamanya berjalan lancar. Beberapa negara, menunjukkan praktik demokrasi yang tidak semestinya. Melalui pengabdian kepada masyarakat bertaraf Internasional ini, pengabdi mencoba berbagi cerita kepada dunia, praktik demokrasi di Indonesia, khususnya bagi generasi muda. Agenda pengabdian kepada masyarakat ini berlangsung di Estonia, pada tanggal 27 Maret hingga 5 April 2023. Metode pengabdian yang digunakan adalah model campuran, dimana ada sesi sosialisasi, diskusi juga materi di kelas. Hasil dari pengabdian ini diharapkan dapat memberikan manfaat bagi pegiat demokrasi di seluruh dunia, bahwa untuk mempertahankan demokrasi dibutuhkan cara dan strategi, seperti: memperkuat nilai-nilai ketuhanan dalam produk hukum, baik di tingkat pusat maupun daerah, mengakomodasi nilai-nilai dan budaya yang berkembang di tengah masyarakat sebagai living law dan memproteksi diri dari nilai yang tidak sesuai dengan jati diri bangsa dan negara.